Unique features of retrovirus expression in F/St mice. - Morse, H C (1982)
F/St mice are unique in producing high levels of both ecotropic and xenotropic murine leukemia virus. The high ecotropic virus phenotype is determined by three or more V (virus-inducing) loci. A single locus for inducibility of xenotropic murine leukemia virus was mapped to chromosome 1 close to, but possibly not allelic to, Bxv-1. Although the high ecotropic virus phenotype is phenotypically dominant, the high xenotropic virus phenotype was recessive in all crosses tested. Suppression of xenotropic murine leukemia virus is governed by a single gene which is not linked to the xenotropic V locus.